PENGGUNAAN METODE INKUIRI DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN - Ervina, Adriana; Kresnadi, Hery; Margiati, KY (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this study was to describe the learning outcome of students at study of Sciences of the properties of objects by using the inquiry method in class IV primary school 09 Sujah, of Bengkayang Regency, and as motivation for teachers to correct any deficiencies (self reformation), making teachers professional and responsible. Data analysis was carried out by following the flow of data analysis including data collection, data reduction, data presentation, and conclusion. The results of the implementation of the settlement act of learning problems with using the inquiry method in each cycle always has risen in the first cycle an average of 68.57 with a value of classical learning completeness in classical 60.71% and the second cycle the average value in the classical 81.79 with the classical learning completeness 96.42%. Improving student learning outcomes from the first cycle to the second cycle is 35.71%. Keywords: Inquiry Method, Learning Science, Student Learning Outcomes